Razvojni status dece i poverenje roditelja u vaspitače u inkluzivnom vrtiću - Buha, Nataša; Jelić, Marija (Specijalna edukacija i rehabilitacija, 2025)
Introduction. Trust forms the foundation of a good partnership between parents and educators and is associated with a range of positive outcomes, not only for the child but also for the parents and professionals. Objective. The aim of this study is to determine the level of parental trust in educators in an inclusive preschool environment, as well as the differences in the level of trust based on the child’s developmental status. Method. The sample included a total of 433 parents of children attending inclusive preschool institutions. Parents of children with various developmental disabilities made up 37.2% of the total sample. Parental trust in educators was assessed using the Trust Scale. Results. The results indicate that parents of children with various developmental disabilities have a lower level of trust in educators compared to parents of children without difficulties, though this difference is not statistically significant. A significantly lower level of trust was recorded among parents of children with multiple developmental disabilities (p ≤ .001). A more detailed analysis revealed that the level of trust among parents of children with sensory impairments and emotional and behavioral problems was comparable to the trust levels of parents of children without disability, while other groups of parents of children with developmental disabilities showed a high percentage of low trust in the areas of communication with educators and support for their child’s development. Conclusion. These preliminary results suggest that educators should be adequately trained and sensitized to recognize and respond to the various needs of children with disabilities and their parents, as well as to foster open and constructive communication with parents.